The Effect of Endorphin Massage on Reducing Labor Pain Intensity During the Active Phase of the First Stage of Labor at Ledokombo Public Health Center, Jember Regency - Yuliastuti, Novi; Keswara, Nila Widya (Sean Institute, 2025)
The most common complaint experienced by mothers during the first stage of labor, active phase, is pain, which can trigger excessive stress and anxiety. This condition may lead to increased respiratory rate and pulse, potentially disrupting oxygen supply from the placenta to the fetus. One simple method that can help reduce labor pain is the endorphin massage technique. The purpose of this study was to examine the difference in pain levels experienced by mothers in the first stage of labor, active phase, before and after receiving endorphin massage. This study used a pre-experimental design with a one-group pretest-posttest approach. It involved 20 laboring mothers in the active phase of the first stage who experienced discomfort ranging from severe (scale 7–9) to very severe (scale 10). Measurements taken before the endorphin massage intervention showed an average pain intensity score of 5 and a maximum of 10. After the endorphin massage was administered, the average pain intensity decreased to 4 with a maximum of 9. There was a notable difference indicating a reduction in pain levels among mothers in the active phase of the first stage of labor before and after receiving endorphin massage intervention.